PENGARUH LINGKUNGAN KERJA DAN KOMPENSASI NON FINANSIALTERHADAP KINERJA PEGAWAI MELALUI KEPUASAN KERJA DI PUSKESMAS KECAMATAN BATANG CENAKU INDRAGIRI HULU - Prayitno Teguh; Ningsih Suryati Dewita; Rifqi Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to determine the effect of the work environment and non-financialcompensation on the performance of Puskesmas employees through employee jobsatisfaction in Batang Cenaku District, Indragiri Hulu Regency. The population in thisstudy were 49 employees at the Puskesmas. Primary data in this study were collectedusing a questionnaire as an instrument to prove the results of the study. To test thehypothesis in this study, Structural Equation Modeling - Partial Least Square (SEM-PLS)was used with the help of the SmartPLS 3.0 program. The sampling technique wascarried out using the Saturated Sampling Method (Census) and 49 PNS Employees (CivilServants) were selected as samples. The results showed that: 1) There is a positive butnot significant influence between the Work Environment on the Job Satisfaction of HealthCenter Staff in Batang Cenaku District, Indragiri Hulu Regency, 2) There is a positiveand significant influence between Non-Financial Compensation on the Job Satisfaction ofthe managers of Batang Cenaku District, Regency Indragiri Hulu, 3) There is a positiveand significant influence between the Work Environment on the performance ofPuskesmas employees in Batang Cenaku District, Indragiri Hulu Regency, 4) There is apositive and significant influence between Non-Financial Compensation on theperformance of Puskesmas employees in Batang Cenaku District, Indragiri HuluRegency, 5) There is a positive and significant influence between satisfaction on theperformance of PUSKESMAS managers in Batang Cenaku District, Indragiri HuluRegency, 6) There is a positive but not significant influence between the WorkEnvironment on performance through employee job satisfaction as i intervening variablesin Batang Cenaku District, Indragiri Hulu Regency, 7) There is a positive and significantinfluence between Non-Financial Compensation on performance through Employee JobSatisfaction as an intervening variable in Batang Cenaku District, Indragiri HuluRegency. Keywords: Work Environment, Non-Financial Compensation, Performance,Satisfaction